2020
DOI: 10.2174/1871520620666200424130934
|View full text |Cite
|
Sign up to set email alerts
|

UBE2L6 is Involved in Cisplatin Resistance by Regulating the Transcription of ABCB6

Abstract: Background: Cisplatin is an important anticancer agent in cancer chemotherapy, but when resistant cells appear, treatment becomes difficult and prognosis is poor. Objective: In this study we investigated the gene expression profile in cisplatin sensitive and resistant cells, and identified the genes involved in cisplatin resistance. Methods: Comparison of gene expression profiles revealed that UBE2L6 mRNA is highly expressed in resistant cells. To elucidate whether UBE2L6 is involved in the acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…ABCB6, an ATP-binding cassette (ABC) transporter group member, is one of the hallmark genes in glycolysis. There are many biological effects of ABCB6, such as protection against oxidative stress [ 31 ], acquired resistance [ 32 , 33 ], and the potential promotion of tumor proliferation [ 34 , 35 ]. Consistently, our results showed that ABCB6 was overexpressed in patients with metastatic OS and a high expression of ABCB6 indicated a low survival rate in OS patients.…”
Section: Discussionmentioning
confidence: 99%
“…ABCB6, an ATP-binding cassette (ABC) transporter group member, is one of the hallmark genes in glycolysis. There are many biological effects of ABCB6, such as protection against oxidative stress [ 31 ], acquired resistance [ 32 , 33 ], and the potential promotion of tumor proliferation [ 34 , 35 ]. Consistently, our results showed that ABCB6 was overexpressed in patients with metastatic OS and a high expression of ABCB6 indicated a low survival rate in OS patients.…”
Section: Discussionmentioning
confidence: 99%
“…CP is a key member of platinum compounds with excellent anti-tumor activity against different cancers such as breast cancer, prostate cancer, bladder cancer, lung cancer, brain tumors, and so on [21][22][23]. The rational reasons for selection of CP are as follows: (1) its anti-tumor activity has been extensively examined, particularly in clinical trials [24][25][26], and (2) the molecular mechanisms and pathways involved in CP resistance/sensitivity have been explored [27][28][29]. Consequently, it has been possible to implicate the process of EMT in drug resistance and directing further studies towards targeting EMT in suppressing resistance developed against CP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…UBE2L6 has been found to be associated with autophagy in esophageal cancer [ 55 ] but has not been previously associated with EOC. Murakami et al [ 56 ] found that cisplatin-resistant cervical cancer cells had overexpressed levels of UBE2L6. While we found no association of UBE2L6 with EOC in the literature, the association with cisplatin sensitivity makes it relevant to the treatment of chemoresistant HGSOC.…”
Section: Resultsmentioning
confidence: 99%